Room temperature organic synthesis - Brahmachari, Goutam (Elsevier, 2015)
Filling a gap in the scientific literature, Room Temperature Organic Synthesis is unique in its authoritative, thorough, and applied coverage of a wide variety of "green" organic synthetic methodologies. The book describes practical, feasible protocols for room temperature reactions to produce carbon-carbon and carbon-heteroatom bond formations including aliphatic, aromatic, alicyclic, heterocycles, and more. Consistently organized for easy access, each selected reaction is discussed in a very compact and structured manner including: reaction type, reaction condition, reaction strategy, catalyst, keywords, general reaction scheme, mechanism (in selected cases), representative entries, experimental procedure, characterization data of representative entries, and references. This book will be a valuable resource for synthetic organic, natural products, medicinal, and biochemists as well as those working in the pharmaceutical and agrochemical industry. Includes more than 300 protocols for a green approach to organic synthesis Provides specific detail about experimental conditions Increases efficiency in the laboratory by eliminating time-consuming literature searches.